2010
DOI: 10.1007/s10194-010-0217-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of headache in Europe: a review for the Eurolight project

Abstract: The main aim of the present study was to do an update on studies on headache epidemiology as a preparation for the multinational European study on the prevalence and burden of headache and investigate the impact of different methodological issues on the results. The study was based on a previous study, and a systematic literature search was performed to identify the newest studies. More than 50% of adults indicate that they suffer from headache in general during the last year or less, but when asked specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
331
11
33

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 459 publications
(419 citation statements)
references
References 84 publications
25
331
11
33
Order By: Relevance
“…17,24,28,37,38,44,45,47 The low rate of headache seen in some studies is perplexing since, within the general population, the estimated lifetime prevalence of headache is approximately 60%-80%, with roughly 40%-60% of individuals experiencing headaches each year. 42,43 This significant disparity probably stems from heterogeneous study methodology, varying definitions of headache, and differing lengths of follow-up. Several studies have used subjective cut-offs that only included patients with "problematic" or "bothersome" headaches.…”
Section: Prevalence Of Headache In Patients With Sporadic Vsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,24,28,37,38,44,45,47 The low rate of headache seen in some studies is perplexing since, within the general population, the estimated lifetime prevalence of headache is approximately 60%-80%, with roughly 40%-60% of individuals experiencing headaches each year. 42,43 This significant disparity probably stems from heterogeneous study methodology, varying definitions of headache, and differing lengths of follow-up. Several studies have used subjective cut-offs that only included patients with "problematic" or "bothersome" headaches.…”
Section: Prevalence Of Headache In Patients With Sporadic Vsmentioning
confidence: 99%
“…24 It is notable that younger age and female sex are also strongly associated with headache within the general population. 42,43 Additionally, it has been shown that anxiety and depression heavily influence headache symptoms. 20,25,33,46 Therefore, the factors that most significantly influence long-term headache in VS are not specific to the diagnosis, but rather are the same predictors for headache in the general population.…”
Section: Clinical Predictors Of Long-term Headache Disabilitymentioning
confidence: 99%
“…4 50% of the general population have headaches during any given year, and more than 90% of them report a lifetime history of headache. 5 The only Italian epidemiological study (PACE study) 6 showed that 52% of men a and 43% of women interviewed suffered from headache in the last year. 7…”
mentioning
confidence: 99%
“…Согласно данным L. J. Stovner, C. Andree (2010), эпизодическая головная боль напряжения встречается в среднем у 62,6% жи-телей Европы, а хроническая головная боль на-пряжения -у 3,3% [8]. В Дании 78% популяции отмечает эпизодическую головную боль напря-жения (возникает не более 15 дней в месяц), 3% страдают хронической головной болью напряже-ния с частотой более 15 дней в месяц на протяже-нии 3 месяцев и более [9].…”
unclassified
“…В Великобритании ми-грень возникает у 15% взрослого населения, чаще у женщин, чем у мужчин (в соотношении 3 : 1) [10]. Европейские эпидемиологические исследования по распространенности основных форм головной боли в популяции, опубликованные в 2010 году, выявили мигрень у 14,7% взрослых пациентов (8% у мужчин и 17,6% у женщин) и у 9,2% детей (5,2% у мальчиков и 9,1% у девочек) [8].…”
unclassified